The interactive effect of gender, residence, and socioeconomic status on early sexual debut among sexually active young adults in Ghana - Asante, Kwaku Oppong; Nketiah-Amponsah, Edward; Andoh-Arthur, Johnny; Ampaw, Samuel (Springer, 2020)
Aim